2020
DOI: 10.1039/d0ta01200a
|View full text |Cite
|
Sign up to set email alerts
|

Polymer photocatalysts with plasma-enhanced activity

Abstract: Plasma treatment was used as a new method to enhance the photocatalytic performance of a hydrophobic polymer photocatalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 34 publications
2
44
0
Order By: Relevance
“…Recent studies have shown that polymer hydrophilicity is an important factor in determining photocatalytic performance. [29][30][31][32] The incorporation of polar moieties such as dibenzo [b,d]thiophene sulfone 33 or nitrogen substituted benzenes 34 into the polymer backbone substantially improves the interaction with water. This in turn enhances the hydrogen evolution activity, partly by stabilizing the charge-separated state that is produced by hole transfer to the hole scavenger following photoexcitation of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that polymer hydrophilicity is an important factor in determining photocatalytic performance. [29][30][31][32] The incorporation of polar moieties such as dibenzo [b,d]thiophene sulfone 33 or nitrogen substituted benzenes 34 into the polymer backbone substantially improves the interaction with water. This in turn enhances the hydrogen evolution activity, partly by stabilizing the charge-separated state that is produced by hole transfer to the hole scavenger following photoexcitation of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Most photocatalysts studied for water splitting have been inorganic semiconductors, but the demonstration that carbon nitride can act as a hydrogen evolution photocatalyst 4 has inspired a large number of subsequent studies [5][6][7][8][9] on sacrificial proton reduction by organic materials. Various organic materials that can be obtained via low temperature condensation reactions have been studied as photocatalysts, 3,[10][11][12] including conjugated microporous polymers (CMPs), [13][14][15][16][17][18][19] covalent triazine-based frameworks (CTFs), [20][21][22][23][24] covalent organic frameworks (COFs), [25][26][27][28][29][30][31][32][33] linear conjugated polymers [34][35][36][37][38][39][40][41][42][43][44][45]…”
Section: Introductionmentioning
confidence: 99%
“…[8,9] Most inorganic photocatalysts are limited by their wide bandgaps (thereby absorbing photons within relatively short spans of wavelengths, leaving most of the solar spectrum inaccessible), [10] while organic semiconductors have rarely been investigated, even though they have many attractive properties (e.g., the capacity to absorb multiple photons, suitable ability to transport charge carriers, and, more particularly, diverse synthetic modularity for tailoring of these properties). [11] Graphene oxide, poly(p-phenylene), conjugated copolymers, [12][13][14] polymer Dots, [15,16] hydrophilic polymers, [17,18] metal-organic frameworks, and graphitic carbon nitride (g-C 3 N 4 , abbreviated as CN) have been investigated most widely as photocatalysts for the drive toward green and sustainable energy production. CN is a particularly promising metal-free photocatalyst for H 2 evolution because it is nontoxic, inexpensive, and highly chemically and thermally stable.…”
mentioning
confidence: 99%